Detecting the Extent of Violating Multiple-Choice Item Writing Rules in the General Secondary Exam in Jordan - Zaza, Haidar (Jordan Journal of Educational Sciences, 2012)
The purpose of this study is to detect violations of the multiple-choice item writing rules in the General Secondary Exam (GSE) in Jordan. A total of 2910 test items administered from 2007 to 2010 were reviewed and evaluated against 18 frequently occurring item-writing flaws.The results showed that 416 (14.3%) of the items contained at least one violation; 366 (12.6%) of the items contained more than one violation, and in total 782 (26.9%) items were violated. Also, the results showed that the most frequent violations were sorting options vertically (67.7%), and arranging options logically, numerically or alphabetically (9.8%). In addition, the percentage of violation for ten rules ranged from 0.2% to 4.3% while six rules were not violated. It is concluded that the GSE in Jordan takes into account the multiple-choice item writing rules. The researcher recommends that the item writing rules should be changed from giving instructions to compulsory commitment.